Robust Evidence for the Breakdown of Standard Gravity at Low Acceleration from Statistically Pure Binaries Free of Hidden Companions - Kyu-Hyun Chae (The Astrophysical Journal)
It is found that Gaia Data Release 3 binary stars selected with stringent requirements on astrometric measurements and radial velocities naturally satisfy Newtonian dynamics without hidden close companions when the projected separation s ≲ 2 kau, showing that pure binaries can be selected. It is then found that pure binaries selected with the same criteria show a systematic deviation from the Newtonian expectation when s ≳ 2 kau. When both proper motions and parallaxes are required to have precision better than 0.005 and radial velocities better than 0.2, I obtain 2463 statistically pure binaries within a “clean” G -band absolute magnitude range. From this sample, I obtain an observed-to-Newtonian predicted kinematic acceleration ratio of ${γ }_{g}={g}_{obs}/{g}_{pred}={1.49}_{-0.19}^{+0.21}$ for acceleration ≲10 ^−10 m s ^−2 , in excellent agreement with 1.49 ± 0.07 for a much larger general sample with the amount of hidden close companions self-calibrated. I also investigate the radial profile of stacked sky-projected relative velocities without a deprojection to the 3D space. The observed profile matches the Newtonian predicted profile for s ≲ 2 kau without any free parameters, but shows a clear deviation at a larger separation with a significance of ≈5.0 σ . The projected velocity boost factor for s ≳ 5 kau is measured to be ${γ }_{{v}_{p}}=1.20± 0.06$ (stat) ±0.05 (sys) matching $\sqrt{{γ }_{g}}$ . Finally, for a small sample of 40 binaries with exceptionally precise radial velocities (fractional errors <0.005), the directly measured relative velocities in the 3D space also show a boost at larger separations. These results robustly confirm the recently reported gravitational anomaly at low acceleration for a general sample.